2011
DOI: 10.1097/gim.0b013e31821705e5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and risk model development for menopausal age in fragile X premutation carriers

Abstract: PURPOSE Women who carry a FMR1 premutation are at risk for fragile X-associated primary ovarian insufficiency (FXPOI) and should be counseled for a potentially reduced fertility. Multiple factors can affect the age of onset and severity of FXPOI. Here, we assessed the predictive power of several factors with menopausal age, a surrogate measure of onset of FXPOI. METHODS Genetic, environmental and reproductive factors were analysed by Cox proportional hazard models in 1,068 women, 385 of fragile X families as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 48 publications
4
35
1
Order By: Relevance
“…Previous studies have reported that activation ratio is not associated with reproductive function (Bione et al, 2006; Murray, 2000; Rodriguez-Ravenga et al, 2009; Spath et al, 2011; Sullivan et al, 2005; Tejada et al 2008). One additional purpose of the present study is to examine the contribution of the activation ratio to the prediction of age at menopause in premutation carrier mothers of children with the full mutation of fragile X syndrome.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported that activation ratio is not associated with reproductive function (Bione et al, 2006; Murray, 2000; Rodriguez-Ravenga et al, 2009; Spath et al, 2011; Sullivan et al, 2005; Tejada et al 2008). One additional purpose of the present study is to examine the contribution of the activation ratio to the prediction of age at menopause in premutation carrier mothers of children with the full mutation of fragile X syndrome.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, the data from the Sherman group’s Atlanta studies were combined with those from a cohort drawn from Nijmegen, the Netherlands (Spath et al, 2011). The Nijmegen sample, ascertained through the Radboud University Medical Center, was drawn from all families in which a proband was diagnosed with FXS between 1984 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…All mice used in this study had ~130 repeats unless otherwise specified. In some cohorts studied, such alleles are associated with the highest risk of FXPOI (Spath et al 2011). Even in cohorts where such alleles are not associated with the very highest risk, the risk of FXPOI remains high (Spath et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Although earlier studies suggested an association between alleles in this size range and FXPOI, larger subsequent studies did not support these initial findings. 8,9 A small number of patients meeting the criteria for FXTAS with FMR1 intermediate alleles have been described, 62 although larger studies are needed to determine the significance of this finding.…”
Section: Fx 312: Intermediate (Gray Zone Inconclusive Borderline)mentioning
confidence: 99%
“…There is no evidence to support an association between high normal and intermediate range FMR1 alleles with a risk of POI. 8,9 Older males and females with premutations are at risk for FXTAS. [10][11][12][13][14][15][16] FXTAS is a late-onset, progressive development of intention tremor and ataxia often accompanied by progressive cognitive and behavioral difficulties including memory loss, anxiety, reclusive behavior, deficits of executive function, and dementia.…”
mentioning
confidence: 99%